Dendrobium officinale polysaccharide-induced neuron-like cells from bone marrow mesenchymal stem cells improve neuronal function a rat stroke model. (December 2021) - Dou, Rengang; Liu, Xue; Kan, Xiuli; Shen, Xianshan; Mao, Jing; Shen, Hongtao; Wu, Jianxian; Chen, Hanlin; Xu, Wanting; Li, Shasha; Wu, Tingting; Hong, Yongfeng
Highlights: A new treatment strategy that can significantly improve recovery from ischemic stroke. A new inducing substance can promote the differentiation of stem cells into nerve-like cells. Polysaccharides can induce stem cells to differentiate into nerve-like cells under the control of Wnt signaling pathway. Neuron-like cells can effectively improve the prognosis of cerebral infarction. Abstract: Various methods have been used to induce the neuronal differentiation of marrow mesenchymal stem cells (MSCs). However, the limited induction efficiency of cells in vitro has restricted their use. Therefore, identifying a simple and efficient treatment method is necessary. Dendrobium officinale is an important traditional Chinese medicine, and its main component, polysaccharides, has many pharmacological activities. However, the effects of D. officinale polysaccharide (DOP) on the neuronal differentiation of bone marrow mesenchymal stem cells (BMSCs) and treatment of ischaemic stroke remain unknown. We found that DOP promoted the neuronal differentiation of BMSCs by increasing the expression levels of neural markers, and the optimal concentration of DOP was 25 μg/mL. Additionally, the Notch signalling pathway was inhibited during the neuronal differentiation of BMSCs induced by DOP, and this effect was strengthened using an inhibitor of this pathway. The Wnt signalling pathway was activated during the differentiation of BMSCs, and inhibition of the Wnt signalling pathway downregulated the expression of neuronal genes. Furthermore, the transplantation of neuron-like cells induced by DOP improved neuronal recovery, as the brain infarct volume, neurologic severity scores and levels of inflammatory factors were all significantly reduced in vivo. In conclusion, DOP is an effective inducer of the neuronal differentiation of BMSCs and treatment option for ischaemic stroke.